ANALISA KINERJA ALAT BERAT PADA PROYEK PEMBANGUNAN JALAN H. E. A. MOKODOMPIT - Iswandi Ases; Fitriah Mas'ud; Umran Sarita (Media Konstruksi : Jurnal Ilmiah Teknik Sipil, 2017)
Abstract Implementing road projects in the region H.E.A Mokodompit, need analysis that good. So machine performance in the implementation of the project, can be resolved properly and on time according to the project.This study aims to determine the optimal amount of heavy equipment and long duration of heavy equipment work in completing each item of work and also to optimize use heavy equipment on the project.The analyslisis of the number needs for optimal weight based researchers are Class B Aggregate Base (Base-B) work is Whell Loader 1 unit, Dump Truck 6 units, Motor Grader 1 unit, Vibrator Roller 1 unit, Water Tank Truck 1 unit, while work of Coat Resistant (Prime Coat) Is Asphalt Sprayer 1 unit and Water Compressor 1 unit and for layer of foundation (AC-BC) is Whell Loader 1 unit, pneumatic Tire Roller 1 unit, and Dump Truck 2 unit.Aggregated result of the analysis time job or duration of any item of work which is derived san summed difference is having 24 hours work. When based on the analysis of researchers is slightly slow than the time based on the time difference in field.  Abstrak Melaksanakan proyek pembangunan jalan di kawasan H.E.A Mokodompit, dibutuhkan analisa kinerja alat berat yang baik, sehingga dalam pelaksanaan proyek tersebut, dapat terselesaikan dengan baik, dan untuk menghitung produktif alat berat dalam proyek tersebut.Hasil analisa jumlah kebutuhan alat berat yang optimal berdasarkan penelitian adalah pekerjaan Lapisan Pondasi Agregat Kelas B (Base-B) adalah Whell Loader 1 unit, Dump Truck 6 unit, Motor Grader 1 1 unit, Vibrator Roller, Water Tank Truck 1 unit. Kemudian untuk (Base- A) adalah Whell Loader 1 unit, Dump Truck 7 unit, Motor Graider I unit, Vibrator Roller 1 unit, Water Tank Truck 1 unit, sedangkan pekerjaan Lapis Resap Pengikat (Prime Coat) adalah Asphalt Sprayer 1 unit dan Air Compressor 1 unit dan untuk lapis pondasi (AC- BC) adalah Whell Loader 1 unit, Pneumatik Tire Roller 1 unit, dan Dump Truck 2 Unit.Hasil anlisa waktu pekerjaan atau durasi setiap item pekerjaan dihasilkan dan dijumlahkan yaitu mengalami selisih waktu 24 jam kerja, dimana berdasarkan hasil penelitan sedikit lebih lama dari pada waktu yang berdasarkan surver dan wawancara.